How to Draw Cats - Murawski, Laura (New York The Rosen Publishing Group's Powerkids Press, 2001)
Describes how to draw various cats, including the saber-tooth cat, Morris the cat, and Goddess Bastet.
Keywords: Cats in art; Drawing - technique